Introduction: Bodily Practices and the European Reformations - Klymenko, Iryna (Reformation, 2025)
This introduction establishes a conceptual and historiographical framework for the present special issue, on “Bodily Practices and the European Reformations.” It charts the development of scholarly interest in the body and embodied religion, questions the lingering tendency to distinguish belief and practice, and suggests that this is partly an intellectual legacy of the Reformation itself. It surveys the common themes that emerge from the essays that comprise this collection. Collectively they demonstrate how the religious transformations of the early modern period shaped, and were shaped by, the ways in which individuals and communities expressed and enacted their faith through the body.